Pain and Analgesia in Children with Cancer after Hemipelvectomy: A Retrospective Analysis - Vamshi R. Revuri; Karen Moody; Valerae Lewis; Rodrigo Mejia; Douglas J. Harrison; Ali H. Ahmad (MDPI AG, 2022)
A paucity of data exists centering on the pain experience of children following hemipelvectomy performed for primary bone and soft tissue sarcomas. In this study, we aimed to describe the incidence, severity, and evolution of perioperative pain and function in pediatric oncology patients undergoing hemipelvectomy, and, additionally, we sought to detail the analgesic regimens used for these patients perioperatively. A retrospective chart review was conducted, studying cancer patients, aged 21 years and under, who underwent hemipelvectomy at MD Anderson Cancer Center (MDACC) from 2018 to 2021. Primary outcomes included the evolution of pain throughout the perioperative course, as well as the route, type, dose, and duration of analgesic regimens. Eight patients were included in the analysis. The mean age at operation was 13 ± 2.93 years. All patients received opioids and acetaminophen. The mean pain scores were highest on post-operative day (POD)0, POD5, and POD 30. The mean opioid use was highest on POD5. A total of 75% of patients were noted to be ambulating after hemipelvectomy. The mean time to ambulation was 5.33 ± 2.94 days. The combination of acetaminophen with opioids, as well as adjunctive regional analgesia, non-steroidal anti-inflammatory drugs, gabapentin, and/or ketamine in select patients, appeared to be an effective analgesic regimen, and functional outcomes were excellent in 75% of patients.